Design of Educational Game Teaching Materials Based on Cognitive Conflict on Particle Dynamics Material - Widia Eka Putri (Physics Learning and Education, 2026)
Conceptual understanding plays a crucial role in physics learning because it enables students to connect theory with real phenomena, build scientific reasoning, and prevent misconceptions. However, the reality of learning shows that students' conceptual understanding, especially of Newton's laws, is still low. This condition calls for innovation in teaching materials, one of which is through the development of educational games based on the cognitive conflict learning model. This study aims to develop a valid and practical cognitive conflict learning model-based physics educational game to improve students' conceptual understanding. The research includes development research using the Plomp model, which consists of preliminary research, development or prototyping, and assessment stages. The research was limited to one-to-one practicality testing. Data were obtained through a preliminary study of students in classes XI F4 and XI F5 taught by physics teachers at SMA Pembangunan Laboratorium UNP. Validation was carried out by three physics lecturers from FMIPA UNP, while practicality testing was carried out on three students in class XI Fase F at the same school. The research instruments included open-ended questionnaires, concept comprehension tests, teaching material needs questionnaires, self-evaluation sheets, validity sheets, and practicality sheets. Data analysis used descriptive, V Aiken, and percentage techniques. The results showed that students needed technology-based teaching materials to improve their concept comprehension. The physics educational game on Newton's Law material was successfully developed with excellent quality. The self-evaluation results were 96 percent, the average validity was 0.93, and the practicality was 90.06 percent, all of which were categorized as very good. The game was declared valid and practical for use in high school physics learning and will be followed up with an effectiveness test of the educational game product.